Bye-laws of the Adventurers of England trading into Hudson's Bay [electronic resource] : passed at a general court held on the 3rd July, 1863. - Hudson's Bay Company. ([London? : s.n., 1863)
Electronic reproduction. Mode of access: Internet. 44